The Impact of Cervical Spine Ailments and Dysfunctions on the Quality of Life of Professionally Active Nurses - Lech Grzelak; Monika Żelazkowska; Agnieszka Szajerska; Mateusz Szostak (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. In the era of contemporary changes and evolution of the nursing profession, changing work standards and ergonomics, the professional group of people suffering from cervical spine problems is growing. So far, little research has been conducted on the occurrence of spine problems and their impact on the quality of life of professionally active nurses.